2007
DOI: 10.1143/jjap.46.4684
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Two-Dimensional Defect-Mode Waveguides in a Sonic/Phononic Crystal

Abstract: Sol modified with diethanolamine was used for the preparation of thick lead zirconate titanate (PZT) films. The deposited films crystallized in the perovskite structure by heating above 600 C. Thick film with 3 m single-coating thickness was obtained using a dip-coating of sol containing PZT powder. The resultant thick films were porous and the pores could not be filled with a cover coating of powder-free sol. The dielectric properties of the thick and porous films prepared using powdercontaining sols were poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Nevertheless, comparing these results with the ones already published indicates that similar results could be achieved for different types of PnCs made of different materials. 30,31 In conclusion, guiding and bending was demonstrated theoretically and experimentally in a planar phononic crystal composed of a square array of circular air cylinders in aluminum. We have shown that a confined guided mode can be realized by careful manipulation of the PnC lattice.…”
mentioning
confidence: 84%
“…Nevertheless, comparing these results with the ones already published indicates that similar results could be achieved for different types of PnCs made of different materials. 30,31 In conclusion, guiding and bending was demonstrated theoretically and experimentally in a planar phononic crystal composed of a square array of circular air cylinders in aluminum. We have shown that a confined guided mode can be realized by careful manipulation of the PnC lattice.…”
mentioning
confidence: 84%
“…We have simulated the behaviors of acoustic waves in DMWGs by the elastic FDTD method. 8 The lattice constant is a = 50Δx and the radius of the acrylic resin cylinders is r = 20Δx, consequently the filling ratio is 0.503, where Δx is the spatial sampling interval for the FDTD calculation.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Visualized observation of the numerical simulations of the wave propagation along DMWG revealed a successive transfer of a kind of localized resonant mode between the point-defects and two good characteristics (1) the guided waves travel along the waveguide without noticeable reflection at input and output, and even at sharp bends of the waveguides, and (2) the waves are well confined around the waveguide with a good transmission of about 0 dB. 9 It was found quite easy to fabricate acoustic waveguides of a bandpass characteristic with sharp perpendicular bends, branch or crossroads, 8 and also two coupled waveguides in a sonic/phononic crystal. 9 A resonant mode localized in a point-defect, named defect-mode, has no capabilities to travel in the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, quite a few exceptional properties of elastic wave propagation were found to exist in man-made periodic heterogeneous structures due to the characteristics of multiple scattering. [1][2][3][4][5][6][7][8][9][10][11][12] Such elastic structures are called phononic or sonic crystals, particularly giving rise to a strong sound attenuation if the wavelength is on the order of the period of the structures (attributed to Bragg scattering). [1][2][3][4][5][6][7][8] In the structures, the frequency ranges where the sound is strongly attenuated are referred to as phononic or sonic band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Such elastic structures are called phononic or sonic crystals, particularly giving rise to a strong sound attenuation if the wavelength is on the order of the period of the structures (attributed to Bragg scattering). [1][2][3][4][5][6][7][8] In the structures, the frequency ranges where the sound is strongly attenuated are referred to as phononic or sonic band gaps. The phenomena of the band gaps, hence, give possible applications to the guiding and filtering of acoustic waves, and the shielding of noise or vibration.…”
Section: Introductionmentioning
confidence: 99%